2000
DOI: 10.1016/s0048-9697(00)00712-9
|View full text |Cite
|
Sign up to set email alerts
|

Methane emission from a simulated rice field ecosystem as influenced by hydroquinone and dicyandiamide

Abstract: A simple apparatus for collecting methane emission from a simulated rice field ecosystem was formed. With no Ž . wheat straw powder amended all treatments with inhibitor s had so much lower methane emission during rice Ž . growth than the treatment with urea alone control , which was contrary to methane emission from the cut rice᎐soil Ž . Ž . system. Especially for treatments with dicyandiamide DCD and with DCD plus hydroquinone HQ , the total amount of methane emission from the soil system and intact rice᎐soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…During the first 30 days of the growing season the N 2 O emission decreased steadily, but markedly increased 50 days after fertilization. It is suggested that due to the decomposition of the wheat straw and the remineralization of newly immobilized N, the NH 4 + concentration in the floodwater of all treatments reached a maximum after 30 days (data not shown, see Xu et al 2000a). Nitrification and subsequent denitrification of this N in the surface soil layers or in the floodwater would induce the pronounced N 2 O emission.…”
Section: Rice Cropping Systemmentioning
confidence: 97%
See 1 more Smart Citation
“…During the first 30 days of the growing season the N 2 O emission decreased steadily, but markedly increased 50 days after fertilization. It is suggested that due to the decomposition of the wheat straw and the remineralization of newly immobilized N, the NH 4 + concentration in the floodwater of all treatments reached a maximum after 30 days (data not shown, see Xu et al 2000a). Nitrification and subsequent denitrification of this N in the surface soil layers or in the floodwater would induce the pronounced N 2 O emission.…”
Section: Rice Cropping Systemmentioning
confidence: 97%
“…Xu et al 2000aXu et al , 2002a. The cumulative N 2 O emissions from the different treatments of the rice cropping system are presented in Table 2.…”
Section: Rice Cropping Systemmentioning
confidence: 99%
“…Urease inhibitors affected CH 4 emission by the positive effect on the redox potential of the rhizosphere and biomass production of rice. DCD, especially in combination with HQ, significantly enhanced CH 4 oxidation in the rice root rhizosphere, particularly between its tillering and booting stages and reduced CH 4 emission profoundly (Xu et al 2000a). The presence of a more highly oxidized rhizosphere would result in a reduction of CH 4 emission from rice field to the atmosphere (Denier Van der Gon and Neue 1996).…”
Section: Yearsmentioning
confidence: 98%
“…However, there are conflicting reports regarding the influence of urease and nitrification inhibitors on CH 4 emission (Cai et al 1994;Xu et al 2000a;Malla et al 2005) and the mechanism of urease inhibitors and nitrification inhibitors on CH 4 emission needs to be considered from three different levels.…”
Section: Yearsmentioning
confidence: 99%
See 1 more Smart Citation